PENGGUNAAN MEDIA DOMAN (DOMINO PENJUMLAHAN) UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS I SDN LIDAH WETAN IV SURABAYA - Silasari, Shofi Putri; Rukmi, Asri Susetyo; Nuraini, Arfiani Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to increase the interest in learning of grade I students at SDN Lidah Wetan IV Surabaya in Mathematics lessons on addition material through the use of doman media (domino addition). The research was conducted in the form of Classroom Action Research with two cycles, and involved grade I students as research subjects. Each cycle consists of four stages, namely planning, implementing actions, observation, and reflection. Media use DOMAN (Domino Penjumlahan) as a learning method is expected to increase students' interest in learning Mathematics. Media DOMAN (Domino Penjumlahan) used in learning to provide learning experiences that interest students. The results showed that the use of media DOMAN (Domino Penjumlahan) effective in increasing students' interest in learning. Each cycle showed an increase in the average student interest score, from cycle I of 24,22 into cycle II of 27,37. This research succeeded in achieving success indicators, namely 87,5% Students achieve a high learning interest score with a minimum score of 25. Thus, the results of this study provide evidence that media use DOMAN (Domino Penjumlahan) can be an effective alternative to increase students' interest in Mathematics subjects addition material.